Management methods and soil cover plants for the cultivation of tutored tomato - Valmorbida, Janice (2020)
The objective of this work was to evaluate the influence of management methods and winter soil cover crops on the tutored tomato yield. The treatments consisted of a combination of two planting methods (conventional and no-tillage) and four winter soil coverings (fallow, oats, turnip and oats + turnip). The nitrogen content (N), the C/N ratio, the dry mass and the N accumulation in the aerial part of the cover plants were evaluated, as well as the tomato yield, in the 2009/10 and 2011/12 harvests. At the end of the harvest, the mechanical resistance to soil penetration was determined using an impact penetrometer. The species of cover plants and the methods of soil preparation did not affect the production of dry mass and total N of the cover plants, with a higher N content for the oat + turnip consortium than for oats, with reduction of C/N ratio, only in 2011/12. Higher commercial tomato yield was observed in conventional planting (79.2 x 65.3t ha-1) in the 2009/10 harvest, in which the no-tillage system presented greater soil resistance to the penetrometer test. In the 2011/12 harvest, the commercial yield was higher in no-till (102.8 x 97.3t ha-1). The coverings of soil with oats and turnip, in intercropped or single cultivation, as well as the winter fallow, did not affect the commercial tomato yield in any of the studied years.